Orbital multilobular osteochondrosarcoma in a dog (Bioscience Journal, 2016)
Retrobulbar tumors may arise from any orbital tissue. Some are primary and others may extend from adjacent structures or derived from metastases. Multilobular osteochondrosarcomas are regarded as slowly growing and potentially malignant neoplasms in dogs. This tumor is of rare occurrence on retrobulbar region. This paper aims to report a rare case of female dog, Shih Tzu, spayed, five-year-old, that was referred to the Hospital of Veterinary Medicine, Federal University of Bahia, Brazil, with an increased volume in the orbital space, after enucleation for exophthalmia of unknown etiology. This animal was evaluated clinic and the diagnosis image (radiography and computed tomography) demonstrated a large formation of bone predominantly in the region of the right orbit and zygomatic arch, with invasion and destruction of adjacent bones. Due to her poor quality of life, the dog was submitted to euthanasia and after necropsy. On gross examination, an encapsulated nodular mass with an irregular surface, measuring 5.6 x 4.6 x 3.9 cm, was located in the right lateral skull, occupying the orbit with displacement of the zygomatic arch. The tumor was identified by histopathology as a malignant mesenchymal neoplasm, multilobular osteochondrosarcoma. Thus, differential diagnoses for exophthalmos should include cancers, including the multilobular osteocondrossarcoma.